Total factor productivity and the propagation of shocks: Empirical evidence and implications for the business cycle - Eric Mayer; Sebastian Rüth; Johann Scharler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
Using a sign restrictions approach, we document that total factor productivity (TFP) moves counter-cyclically in the aftermath of supply and demand side shocks. To interpret our empirical results, we conduct counter-factual simulations, based on a New Keynesian DSGE model in which TFP fluctuates endogenously due to time-varying labor effort. The simulations show that the decline in the output gap, following an adverse shock, is dampened by the endogenously improving TFP as long as the nominal interest rate remains strictly positive during the downturn. If the economy hits the zero lower bound, the decline in the output gap is amplified when TFP improves endogenously.
Keywords: E24; E30; E32; E40; 330; TFP; labor effort; zero lower bound